Streamlining Transport Management: The Evolution of Machine-to-Machine Communication - S. A. Patil; Shruti Autade; Vaishnavi Dahei; Rutuja Gaikwad; Diksha Pawar (International Journal of Electrical and Communication Engineering Technology, 2024)
Every transportation industry, as is well known, has its own paperwork that employees of the organisation can complete. There is a lot of paperwork in the transport business. The user will be able to oversee multiple tasks with this way. Additionally, the user can track orders and inspect their goods. By using this method, the user will be able to work more efficiently and save time and energy. It involves a variety of methods and resources needed to complete the project successfully. This method will assist users in scheduling and planning more effectively, saving time and energy, and producing work that is more productive. A system for transportation management could be a type of software that aids companies in organising and carrying out the transportation of their products. It complies with regulations and might aid them in keeping track of their paperwork.
Keywords: Automation; Client Satisfaction; Services Provided; Transport Management System; online platform